ZMYND11 variants are a novel cause of centrotemporal and generalised epilepsies with neurodevelopmental disorder. Issue 4 (16th July 2021) - Oates, Stephanie; Absoud, Michael; Goyal, Sushma; Bayley, Sophie; Baulcomb, Jennifer; Sims, Annemarie; Riddett, Amy; Allis, Katrina; Brasch‐Andersen, Charlotte; Balasubramanian, Meena; Bai, Renkui; Callewaert, Bert; et al.
Abstract: ZMYND11 is the critical gene in chromosome 10p15.3 microdeletion syndrome, a syndromic cause of intellectual disability. The phenotype of ZMYND11 variants has recently been extended to autism and seizures. We expand on the epilepsy phenotype of 20 individuals with pathogenic variants in ZMYND11 . We obtained clinical descriptions of 16 new and nine published individuals, plus detailed case history of two children. New individuals were identified through GeneMatcher, ClinVar and the European Network for Therapies in Rare Epilepsy (NETRE). Genetic evaluation was performed using gene panels or exome sequencing; variants were classified using American College of Medical Genetics (ACMG) criteria. Individuals with ZMYND11 associated epilepsy fell into three groups: (i) atypical benign partial epilepsy or idiopathic focal epilepsy (n = 8); (ii) generalised epilepsies/infantile epileptic encephalopathy (n = 4); (iii) unclassified (n = 8). Seizure prognosis ranged from spontaneous remission to drug resistant. Neurodevelopmental deficits were invariable. Dysmorphic features were variable. Variants were distributed across the gene and mostly de novo with no precise genotype–phenotype correlation. ZMYND11 is one of a small group of chromatin reader genes associated in the pathogenesis of epilepsy, and specifically ABPE. More detailed epilepsy descriptions of larger cohorts and functional studies might reveal genotype–phenotype correlation. The epileptogenic mechanism may be linked to interaction with histone H3.3. Abstract : Variants in the intellectual disability and candidate autism gene ZMYND11 is a novel cause of centrotemporal epilepsy syndromes: Atypical Benign Partial Epilepsy and Rolandic epilepsy, as well as juvenile generalised and infantile epilepsy syndromes.